Effects of Added Defusion or Feed Aid on Finishing Pig Growth Performance from 45 to 243 lb - D. Shawk; S. S. Dritz; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,188 pigs (PIC 359 × 1050; initial BW 45.1 lb) were used in a 112-d growth trial to determine the effects of Defusion (Provimi, Brooksville, OH) or Feed Aid (NutriQuest, Mason City, IA) on finishing pig performance from 45 to 243 lb in a commercial setting. Pens of pigs were blocked by BW and then randomly assigned to 1 of 4 dietary treatments in a completely randomized block design with 27 pigs per pen and 11 pens per treatment. Dietary treatments were fed in a 4-phase feeding program from approximately 45 to 83, 83 to 136, 136 to 196, and 196 to 243 lb BW. The four treatment diets included a positive control (corn-soybean meal-based diet), a negative control (corn-soybean meal-based diet containing 40% dried distillers grains with solubles), or the negative control diet with either 0.25% Defusion or 0.25% Feed Aid. Mycotoxin analysis indicated the deoxynivalenol (DON) concentrations of the treatment diets varied by treatment and phase, but all concentrations were less than 1 ppm. From d 0 to 28, pigs fed the negative control diet or the diet containing Feed Aid had decreased (P<0.05) ADG and d 28 BW compared to those fed the positive control, with pigs fed Defusion treatment intermediate. Pigs fed the positive control diet had greater (P<0.05) ADFI compared to other diets. There was no evidence of difference for F/G. From d 28 to 56, pigs fed the positive control diet had greater (P<0.05) ADG and d 56 BW compared to the other dietary treatments. Pigs fed diets containing Feed Aid or Defusion had greater (P<0.05) ADG compared to the negative control. Average daily feed intake was not influenced by dietary treatments. Pig fed the negative control diet had poorer (P<0.05) F/G when compared to the other dietary treatments. There were no differences in performance from d 56 to 112. Overall, pigs fed the positive control had greater (P<0.05) ADG and final BW when compared to the other dietary treatments, with no evidence of differences in ADFI or F/G. In conclusion, the addition of Defusion improved growth rate during the first two phases of the study and Feed Aid improved growth rate during the second phase. However, neither feed additive improved overall growth performance of finishing pigs when the dietary DON concentration was less than 1 ppm.
Keywords: deoxynivalenol; preservatives; finishing pig; sodium metabisulfite; vomitoxin